SUB-ACUTE TOXICITY STUDY OF ETIMICIN SULPHATE IN WISTAR RAT (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
The aim of the present study was to evaluate subacute toxicity of etimicin sulphate on wistar rat. Results from the present study have elucidated that treatment of etimicin sulphate exerts no significant signs of toxicity at any dose level used in the study. Physical, biochemical as well as hematological parameters was unaltered throughout the study. Histopathology of all organs confirmed no significant alteration at any dose levels. The results of study have suggested there was no obvious toxicity observed with the treatment of etimicin sulphate. It was found to be safe alternative for various severe infections.